I could live here forever - Halperin, Hanna (Viking, 2023)
"By the author of Something Wild, a gripping portrait of a tumultuous, consuming relationship between a young woman and a recovering addict When Leah Kempler meets Charlie Nelson in line at the grocery store, their connection is immediate and intense. Charlie, with his big feelings and grand proclamations of love, captivates her completely. But there are peculiarities of his life-he's older than her but lives with his parents; he meets up with a friend at odd hours of the night; he sleeps a lot and always seems to be coming down with something. He confesses that he's a recovering heroin addict, but he promises Leah that he's never going to use again. Leah's friends and family are concerned. As she finds herself getting deeper into an isolated relationship, one of manipulation and denial, the truth about Charlie feels as blurry as their time together. Even when Charlie's behavior becomes increasingly erratic, when he starts to make Leah feel unsafe, she can't help but feel that what exists between them is destined. Charlie is wide open, boyish, and unbearably attractive. The bounds of Leah's own pain-and love-are so deep that she can't see him spiraling into self-destruction. Hanna Halperin writes with aching vulnerability and intimacy, sharply attuned to Leah's desire for consuming, compulsive connection. I Could Live Here Forever exposes the chasm between perception and truth to tell an intoxicating story of one woman's relationship with an addict, the accompanying swirl of compassion and codependence, and her enduring search for love and wholeness"--